The application of novel methods of Animal Barrier Screen and Kelambu Trap for mosquitoe’s surveillance in South and West Sulawesi, Indonesia - Nur Rahma; Hajar Hasan; Arini Ratnasari; Isra Wahid (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rahma N, Hasan H, Ratnasari A, Wahid I. 2020. The application of novel methods of Animal Barrier Screen and Kelambu Trap for mosquitoe’s surveillance in South and West Sulawesi, Indonesia. Biodiversitas 21: 4787-4794. Mosquito’s surveillance requires effective protocols to catch mosquitoes in a large number of species and individuals while safe for humans. The effectiveness of two novel trap methods was compared during dry and wet seasons in rural (Maros), semi-urban (North Toraja) both in South Sulawesi Province, and rural with coastal areas (Pasangkayu) in West Sulawesi Province. Animal Barrier Screen (ABS) is a barrier screen placed near livestock, while Kelambu Trap (KT) is an innovative form of mosquito net. Both trap innovations showed effective in catching mosquitoes, but ABS was more effective in trapping the mosquitos (8,589 individuals) than KT (8,350 individuals). In contrast, the species caught were more diverse in KT (43 species, nine genera) than that in ABS (36 species, seven genera). During the wet season, ABS and KT caught 4,848 individuals (27 species, five genera) and 4,749 individuals (36 species, eight species), respectively. Mosquitoes were the most abundant in Northern Toraja (6,338 individuals), followed by in Maros (5,566 individuals) then Pasangkayu (5,035 individuals), but mosquito diversity was the highest in Pasangkayu (nine genera, 33 species) compared to that in Northern Toraja (six genera, 27 species) and Maros (five genera, 25 species). Based on the effectiveness of this trap, innovative insecticide can be added into ABS and KT traps then placed in the field. The number of mosquitoes can be significantly reduced so that it can also lower the potential spread of the mosquitoes-born viruses.